Analisis Masalah Sampah Penyebab Kebakaran di Gunung Andong - Zulfa, Alya Rana; Damayanti Mulyono, Kiki; Rahayu, Rina (Jurnal Ekologi, Masyarakat dan Sains, 2024)
Mount Andong is a natural tourist destination in Magelang Regency, Central Java, Indonesia. Mount Andong faces serious challenges related to waste management and the risk of forest fires. This research provides an overview of the condition of Mount Andong regarding the increasing accumulation of waste, especially plastic waste which is detrimental to the ecosystem and natural sustainability. Apart from the waste problem, Mount Andong is experiencing the threat of forest fires, both due to natural factors such as extreme weather and high temperatures, as well as human negligence such as burning agricultural land and carelessly throwing away cigarette butts. The fire on August 10 2023 is an example of the cause of significant forest damage. This research focuses on forest fire mitigation and management as an effort to achieve sustainability on Mount Andong. Integrated steps are needed including improving waste management infrastructure, educational campaigns, and strict law enforcement regarding illegal waste dumping. This research emphasizes the importance of collaboration between the government, community and related parties to manage Mount Andong sustainably, protect its ecosystem and create a better future.